2013
DOI: 10.1177/0956462413489276
|View full text |Cite
|
Sign up to set email alerts
|

Persistent genital arousal and restless genitalia: sexual dysfunction or subtype of vulvodynia?

Abstract: We conducted a literature review of patients' conditions described under persistent genital arousal disorder and restless genital syndrome, vulvodynia and male genital skin pain of unknown aetiology (penoscrotodynia). Our aim is to improve the understanding of the condition, unify nomenclature and promote evidence-based practice. The most prominent symptom in persistent genital arousal disorder and restless genital syndrome is a spontaneous, unwelcomed, intrusive and distressing vulval sensation. There are sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
1
28
0
3
Order By: Relevance
“…Health and Behavior indicate that about 5% of men and about 30% of women in the United States report some degree of pain during their most recent sexual experience [1]. Women's experiences of genital pain during sexual activities appear to be a common outcome of multiple etiologic pathways related to hormonal status (e.g., menopause, lactation), vulvar dermatoses (e.g., lichen sclerosus), gynecological health (e.g., endometrioisis), infections (e.g., bacterial vaginosis or candidiasis), medications (e.g., reduced vaginal lubrication from hormonal contraception), and mechanical issues (e.g., tight genital fit between partners, vaginal penetration despite insufficient vaginal lubrication, etc), or may have unclear origins, perhaps resulting in a diagnosis of vulvodynia [2][3][4][5][6][7][8][9][10][11][12][13]. Vulvodynia, dyspareunia, and other types of genital pain can create substantial personal distress to patients and relationship partners and have been linked with lower scores on measures of sexual satisfaction [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Ata From the 2009 National Survey Of Sexualmentioning
confidence: 99%
“…Health and Behavior indicate that about 5% of men and about 30% of women in the United States report some degree of pain during their most recent sexual experience [1]. Women's experiences of genital pain during sexual activities appear to be a common outcome of multiple etiologic pathways related to hormonal status (e.g., menopause, lactation), vulvar dermatoses (e.g., lichen sclerosus), gynecological health (e.g., endometrioisis), infections (e.g., bacterial vaginosis or candidiasis), medications (e.g., reduced vaginal lubrication from hormonal contraception), and mechanical issues (e.g., tight genital fit between partners, vaginal penetration despite insufficient vaginal lubrication, etc), or may have unclear origins, perhaps resulting in a diagnosis of vulvodynia [2][3][4][5][6][7][8][9][10][11][12][13]. Vulvodynia, dyspareunia, and other types of genital pain can create substantial personal distress to patients and relationship partners and have been linked with lower scores on measures of sexual satisfaction [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Ata From the 2009 National Survey Of Sexualmentioning
confidence: 99%
“…They further reported a "clustering" of these symptoms and theorized they could be lumped into a condition they deemed restless genital syndrome (RGS), a more complex syndrome that encompasses RLS, PGAD, overactive bladder and urethra hypersensitivity. Markos and Dinsmore (2013) concurred with the notation of similarities between PGAD and RGS and went on to suggest that these similarities can also be found in vulvodynia, a condition involving chronic pain of the external genital region. In their 2013 manuscript, Markos and Dinsmore suggested that PGAD and RGS be considered subtypes of vulvodynia and argued that it should be reclassified as a pain disorder as opposed to a sexual dysfunction, which appears to be based upon their interpretation of the similarity in symptoms and the evolving definition of vulvodynia over the past few decades.…”
Section: Pelvic Congestion and Varicesmentioning
confidence: 64%
“…Because these women were bathing multiple times per day due to their persistent arousal and orgasms, and were hesitant to discuss their concerns due to fear of being seen as hypersexual, they were instead treated for OCD and subsequently received no relief. Fear, guilt, shame, and embarrassment have been cited across the literature as the potential reasons behind low reporting levels of PGAD (Markos & Dinsmore, 2013;Leiblum, 2008;Mahoney & Zarate, 2007).…”
mentioning
confidence: 99%
“…Her symptoms were very similar to those previously described in RGS and her dramatic response to pramipexole supports this diagnosis. 3,6,7 The intrusive genital symptoms in RGS may be perceived as a discomfort, irritation, tingling, itching, congestion, and pain. Although most patients have difficulty describing their symptoms, 3 the account is very similar among patients, reinforcing the organic nature of this disorder.…”
Section: Discussionmentioning
confidence: 99%